IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN (SIMPEG) DI BADAN KEPEGAWAIAN PENDIDIKAN DAN PELATIHAN DAERAH KOTA SAMARINDA - Dwi Cipta Widyawan; Adam Idris (Jurnal Administrative Reform, 2021)
This article describes the Implementation of the Personnel Management Information System (SIMPEG) at the Regional Education and Training Personnel Board. This study uses a descriptive qualitative approach with data collection through observation, documentation, and interviews. This study uses data analysis developed interactive data. The results showed that the implementation of SIMPEG in BKPPD was not optimal. This is because the implementation of socialization was not effective, human resources were less competent, the level of commitment held by BKPPD employees was still low, and there was no SOP in implementing SIMPEG.Keywords: implementation, public policy, information systems, staffing